Las artes escénicas para la integración social en el proceso de enseñanza y aprendizaje en los estudiantes del séptimo grado de la escuela de Educación Básica “General Quisquis” - Chilan Santana, Ángel David (2023)
The present research aimed to propose didactic strategies in the classroom using performing arts to school coexistence at seventh grade paralel “A” of basic education school "General Quisquis" Latacunga city, Cotopaxi province. Through research whose purpose is to raise awareness and encourage the application of creative strategies of performing arts for integration social development in the classroom. Since, the performing arts for social integration in the classroom take a relevant aspect in education, with its many facets such as: theater, dance, puppets and more, which strengthens integral development of the child which, offer to the student the opportunity to express himself, communicate helping socialization. The methodology was based on the interpretative paradigm and therefore on qualitative approach, research that allowed to understand the reality of the educational context, the inductive method was applied, consequently the information was analyzed in a particular way. The methodological design was based on content analysis, since information processing was carried out using descriptive analysis arrays. The observation technique was applied with the instrument that was the observation guide applied to the students and a teacher, with a 38 students’ sample, 1 teacher and an authority. The achieved results were the development analysis of performing arts educational context. This information will provide scope of a direct impact on society to improve coexistence in basic education school and in turn will improve methodological strategies in teachers.